Implementasi Akad Rahn di Lembaga Keuangan Syariah - Mulyono (Universitas Muhammadiyah Surabaya, 2025)
Pegadaian Syariah utilizes rahn contracts as one of the products and contracts used by Islamic financial institutions in Indonesia in their operational activities. Nevertheless, fiqh analysis is carried out to avoid impermissible violations. This is because one of the basic principles of Usul Fiqh states that any transaction is permissible unless there is clear evidence that the transaction violates sharia law. In practical terms, the main aspects of the rahn contract, namely marhun, marhun bih, shighah, and